Music and the Child’s Emotional World - Romih, Tamara (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter highlights the importance of music's influence on children's emotional development. Participation in musical activities, such as singing, playing instruments, or listening to music, enables children to express and understand emotions while fostering emotional intelligence. Music education enhances emotional awareness and social skills, including empathy, prosocial behavior, and cooperation, while also boosting motivation and concentration. Numerous studies confirm that music positively impacts self-esteem, self-regulation, and reduces aggressive behavior. Music therapy, whether through active playing or listening, employs techniques such as mirroring, matching, and reflecting to effectively address emotional and behavioral challenges, stimulate creativity, and improve interpersonal relationships. Despite its wide-ranging positive effects, it is essential to consider children's individual needs when using music. Music serves as a powerful tool for fostering emotional maturity and providing holistic support for children's development.